Analisis Kepuasan Penggguna Pada Layanan Aplikasi Mobile Jaminan Kesehatan Nasional (JKN) Menggunakan Metode User Experience Questionnaire (UEQ) - Achlis Amalia Masruroh; Ratna Juita; Bertha Pangaribuan (INFORMAL: Informatics Journal, 2023)
Although application mobile JKN would facilitate the public. However, until now has a view on the level of satisfactiom users application mobile JKN particulary in the area of west Papua. Reseach objectives to be evalution when do for improve te weaknesses and shortage of system. Raising the level of satisfaction mobile users JKN. The use writer method user experience questionnaire (UEQ) to assess the variable UEQ: attractiviness, clarity, efficiency, the reliability of, stimulation and novelty. The result of the research by the number 117 respondents from 5 administrative areas west papua, category above average on a scale attractiviness with the 1.22. Scale clarity with the 1.13 to a category bellow average. Scale efficiency the average value of 1.42 with category above average. Scale the accuracy of get result the average score 2.04 to a category excellent. The stimulation average scoring 1.16 category above average. The last a novelty average 1.85 with excellent categories.